2009
DOI: 10.1093/ndt/gfp172
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate is related to carotid intima-media thickness in middle-aged adults

Abstract: Even a minor deterioration in renal function was independently associated with increased cIMT in the middle-aged male population and in the postmenopausal women. This finding underlines the importance of early detection of subjects with mildly decreased kidney function and the aggressive management of atherosclerotic risk factors in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
2
17
0
4
Order By: Relevance
“…between low GFR and increased IMT. 15,16 The conflicting results may reflect shortcomings of the GFR assessments, as all these studies used GFR estimates rather than measured GFR. Two Asian studies of GFR and plaques also showed differing results.…”
Section: Discussionmentioning
confidence: 99%
“…between low GFR and increased IMT. 15,16 The conflicting results may reflect shortcomings of the GFR assessments, as all these studies used GFR estimates rather than measured GFR. Two Asian studies of GFR and plaques also showed differing results.…”
Section: Discussionmentioning
confidence: 99%
“…One in five diabetic patients progresses to end-stage renal disease within 20 years of nephropathy onset [6]. Cardiovascular complications start early in renal disease with even minor renal deterioration being associated with arterial thickening [7]. Current therapies may not arrest renal function decline and there is an urgent need for new targets and interventions [8], as renal failure and associated cardiovascular disease increase mortality rates [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sharing of established cardiovascular risk factors – such as age, gender, blood pressure, cholesterol, smoking and diabetes – can explain some, but not all excess stroke risk in patients with CKD 3 . Sharing of pathophysiological correlates of vascular disease including carotid atherosclerosis 7 , arterial stiffness 8 , and cerebral white matter hyperintensity (WMH) lesions 9 also appear to explain an additional component, but not all of the excess risk.…”
Section: Introductionmentioning
confidence: 99%